The Sleep of Shift Workers in a Remote Mining Operation: Methodology for a Randomized Control Trial to Determine Evidence-Based Interventions - Maisey, Gemma; Cattani, Marcus; Devine, Amanda; Lo, Johnny; Dunican, Ian C. (Frontiers in Neuroscience, 2021)
Shiftworkers frequently experience sleep loss (<6 hrs. following nightshift), due to the circadian misalignment resulting from the sleep-wake patterns of their roster cycle. Within a mining operation, this sleep loss may have significant consequences due to fatigue, including an increased risk of accidents and chronic health conditions. This study aimed to (i) determine the efficacy of an intervention that comprises a sleep education program and biofeedback through a smartphone app on sleep quality, quantity and alertness (ii) determine the potential prevalence of sleep problems and disorders, and (iii) quantify and describe the sleep habits and behaviors of shiftworkers in a mining operation. This study consisted of a randomized controlled trial whereby eighty-eight shiftworkers within a remote mining operation were randomized to a control group or one of three different treatment groups that were: (i) a sleep education program, (ii) biofeedback on sleep through a smartphone app, or (iii) a sleep education program and biofeedback on sleep through a smartphone app. This study used wrist-worn activity monitors, biomathematical modelling, and a survey instrument to obtain data on participants sleep quantity, quality, and alertness. A variety of statistical methods were used to determine the prevalence of sleep problems and disorders and associations with body mass index, alcohol, and caffeine consumption. A repeated-measures ANOVA was used for the dependent sleep variables assessed at baseline and post-intervention for the control group and intervention groups, as well as between groups to determine changes. The findings from this study will contribute to the current understanding of sleep and alertness behaviors, and sleep problems and disorders amongst shiftworkers. Importantly, the results may inform fatigue policy and practice on interventions to manage fatigue risk within the mining industry. This study protocol may have a broader application in other shiftwork industries, including oil and gas, aviation, rail, and healthcare.